Scale in Area-Class Mapping - Zhang, Jingxiong; Atkinson, Peter; Goodchild, Michael F. (Scale in Spatial Information and Analysis, 2014)
As indicated at the beginning of Chapter 9, scale issues in terrain analysis and area-class mapping are important topics for geospatial research and applications, for at least two good reasons. One is that terrain analysis and area-class mapping are key components in many spatial problem-solving scenarios, in particular those concerning scale and scaling in spatial analysis and modeling. The other is the impressive accumulation of research achievements in terrain analysis and area-class mapping, which can shed light on further research on related subjects. Therefore, this chapter seeks to answer questions about scale and scaling in area-class mapping, continuing the previous discussion of terrain analysis.